Exploring patient experiences of participating in a real and sham dry cupping intervention for nonspecific low back pain: A qualitative study. - Hugo Jário Almeida Silva; Mariana Arias Avila; Kamilla Maria Sousa Castro; Yago Tavares Pinheiro; Caio Alano Almeida Lins; Germanna Medeiros Barbosa; Marcelo Cardoso de Souza (PLoS ONE, 2022)
Background The current quality of evidence supporting dry cupping for individuals with chronic low back pain (CLBP) is low and suggests that nonspecific factors impact experiences reported by patients. Therefore, this study assessed the impacts of social and professional support on the experience of individuals with CLBP treated with dry cupping or sham. Method This is an observational study with qualitative approach. Twenty-four individuals with CLBP who received dry cupping or sham in a previous clinical trial were invited. Data was collected using a semi-structured interview conducted by a trained researcher. Content analysis was used to analyze experiences, systematic procedures, and description of the content of messages. The dimensions of "pain", "general perceptions", and "perceived social and professional support" guided the analysis. Results Answers of both groups converged on similar perceptions, especially regarding pain. Physical condition was the most fragile aspect. We also observed an influence of perceived social and professional support on painful symptoms. Thus, the experience of individuals with CLBP treated with dry cupping or sham indicated that factors related to social and professional support impacted results. Conclusions We observed that individuals with CLBP reported similar perceptions of the effects of dry cupping or sham treatment, indicating that contextual factors may influence the perception of these individuals regarding the treatment received.